Topographical Challenges and Cost Risk Management in Road Construction: Integrating Design Analysis and Unit Price Method (AHSP) in Hilly Areas of Indonesia - Rustam Rustam; Budi Witjaksana; Jaka Purnama (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Road construction in hilly regions of Indonesia presents complex technical and financial challenges due to extreme topographical variations. This study examines the integration of technical design analysis with the Indonesian Standard Unit Price Method (AHSP) to improve cost estimation accuracy and risk management. Using the Batauga–Sampolawa road project in South Buton Regency as a case study, the research analyzes how longsection and cross-section designs influence earthwork volumes and subsequent cost structures. Results indicate that hilly topography necessitates significant slope stabilization measures and unbalanced cut-fill volumes, directly impacting cost distribution. Through AHSP-based cost projection for 2025, the study identifies critical risk factors including fuel price volatility, material classification uncertainties, and equipment productivity in steep terrain. The research demonstrates that an integrated design-cost approach enables more realistic budgeting and proactive risk mitigation in hilly road projects. Recommendations include the adoption of digital terrain modeling, AHSP adjustment factors for hilly conditions, and contingency planning for geotechnical uncertainties.